Preferred futures: Replacing all materials with wood : Futures triangle in researching branding strategies in forestry - Allenius, Päivi (My University, 2024)
This thesis explores the role of climate change in the branding strategies of forestry companies and examines their future perspectives on brand building. Recognizing that brand development is a long-term endeavor, this research employs Sohail Inayatullah’s Futures Triangle to analyze how case companies integrate their views on the past, present, and future into their branding efforts. The study conceptually addresses branding, climate change as a wicked problem, and futures triangle theory. Forestry companies, leveraging nature as their core material, prominently feature sustainability in their branding. This thesis aims to delve into the use of wicked problems in brand building and assess how Inayatullah’s Futures Triangle can guide forward-looking branding strategies within the forestry sector. The research employs a qualitative methodology, encompassing desk research and semi-structured interviews with key representatives from UPM, Stora Enso, and Metsä Group. The desk research focuses on how these companies address climate change in their branding and communication strategies, analyzing their differentiation tactics through company websites and annual reports. The semi-structured interviews seek to uncover the tension between economic growth and sustainability goals, and to explore the future of branding through Inayatullah’s six pillars of foresight. This section aims to reveal how climate change influences brand identity, purpose, mission, values, messaging, differentiation, and overall brand experience. Through this research, the thesis provides a framework for addressing climate change and developing sustainable branding strategies. By integrating foresight methodologies, the study offers insights into how companies can anticipate future trends, challenges, and opportunities, enabling them to align their branding efforts with the evolving environmental landscape. Inayatullah’s six pillars of foresight serve as a foundational tool for envisioning diverse scenarios and crafting adaptable strategies essential for contemporary branding.
Keywords: futures studies, branding, climate change, six pillars, Inayatullah, futures triangle